Analisis Penggunaan Kanyuu Hyougen Dalam Anime Kaguya-sama wa Kokurasetai: Tensai-tachi no Renai Zunousen - Febri Wahyu Nasta; Meira Anggia Putri (Universitas Negeri Padang, 2022)
This study aims to describe the variations and principles of politeness in the use of kanyuu hyougen in the anime kaguya-sama wa kokurasetai: tensai-tachi no renai zunousen. This type of research is a qualitative research with descriptive method. The data of this study is a dialogue containing kanyuu hyougen and the data source used is the anime kaguya-sama wa kokurasetai: tensai-tachi no renai zunousen episodes 1 to 10. Tthe results of this study showed that there were 35 data of kanyuu hyogen which were classified into 3 forms; 1) ishi no hyougen in the form of invites 27 data; 2) ishi no hyougen in the form of question 5 data; 3) hitei gimon no katachi 3 data. Then based on principle of politeness, there were 22 data which were accordance with the principles of politeness and 13 data which were contrary to the principles of politeness.